The use of mobile technologies for learning in higher education: Students' readiness - Lee, Cheng Ean Catherine *; Leow, Serena Wai Yee *; Kong, Xiang Jie * (School of Media and Communication, Taylor's University Malaysia, 2020)
A rapid evolution of technologies and their proliferation in the education system has created a new paradigm of learning with universities embarking on the integration of mobile technologies in higher education. As a result, mobile learning has emerged as a new way of learning. Mobile learning utilises mobile technologies such as smartphones, laptops, tablets and the Internet, allowing students to learn anywhere and access learning resources anytime. To ensure the successful implementation of mobile learning in higher education, it is imperative to understand students’ readiness for using mobile technologies to learn. This paper examines whether undergraduate students of a private university are ready to adapt to the mobility of learning through the use of mobile technologies. A quantitative research approach was adopted. Data was collected from a sample of 234 students of a private university using questionnaires. The descriptive statistics analysis shows that students were fairly comfortable (61.1%, M=3.17) with the use of mobile technologies for learning purposes (98.3%), specifically for accessing and downloading online journals (82.5%) and searching for information (82.1%). Most students somehow agreed that products and services that use technologies were much more convenient to use (M=3.75) and they were open to learning new and different technologies (M=3.71); however, students were only moderately ready for mobile learning if it is were to be implemented by their university (M=3.32). This study concludes that students are ready to use technology as they are fairly comfortable with the use of mobile technologies, yet they are only moderately ready to adopt M-Learning. However, despite demonstrating an interest towards mobile technologies used for learning, the students are still not quite ready to adopt M-Learning in higher education. The present study contributes to a growing body of empirical research about the mobile technologies used for learning in Malaysian higher education and recommends that the Ministry of Education assesses the prospect of applying mobile technologies for learning in higher education institutions.